MEASURING VOCABULARY SIZE OF SIXTH SEMESTER STUDENTS OF ENGLISH STUDY PROGRAM OF UNIVERSITAS RIAU - Sindi Yunika; Jismulatif Jismulatif; Masyhur Masyhur (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This research is a descriptive-quantitative research design which aimed to investigate the vocabulary size of English study program students of Universitas Riau. The subjects of the study were the sixth-semester students majoring in English study program of Universitas Riau. Forty sample students were chosen using proportionate stratified random sampling. Students vocabulary size was measured Using Vocabulary Size Test created by Nation P. in 2007. The findings of this study revealed that the students knew about 8,080 word families. This result showed that the participants had good vocabulary mastery. Based on nation 2006 the mean score of students of English study program of Universitas Riau in sixth-semester were able to read complicated English text. In other words, sixth-semester students of English study program of Universitas Riau already capable to read scientific paper and can start to write thesis for their final task.Key Words: Vocabulary, Vocabulary Size Test, English Study Program.